2015
DOI: 10.1186/s13550-015-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4′-[methyl-11C]thiothymidine (11C-4DST) and 3′-deoxy-3′-[18F]fluorothymidine (18F-FLT) PET/CT in human brain glioma imaging

Abstract: Background3′-deoxy-3′-[18F]fluorothymidine (18F-FLT) has been used to evaluate tumor malignancy and cell proliferation in human brain gliomas. However, 18F-FLT has several limitations in clinical use. Recently, 11C-labeled thymidine analogue, 4′-[methyl-11C]thiothymidine (11C-4DST), became available as an in vivo cell proliferation positron emission tomography (PET) tracer. The present study was conducted to evaluate the usefulness of 11C-4DST PET in the diagnosis of human brain gliomas by comparing with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Toyota et al evaluated 4DST uptake and proliferative activity in 20 patients with gliomas, including 11 recurrent gliomas [10]. They showed a weak correlation between 4DST T/N ratio and Ki-67 index [10]. The present study also showed a weak correlation between 4DST T/N ratio and Ki-67 index in newly diagnosed gliomas.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Toyota et al evaluated 4DST uptake and proliferative activity in 20 patients with gliomas, including 11 recurrent gliomas [10]. They showed a weak correlation between 4DST T/N ratio and Ki-67 index [10]. The present study also showed a weak correlation between 4DST T/N ratio and Ki-67 index in newly diagnosed gliomas.…”
Section: Discussionsupporting
confidence: 47%
“…In a previous study, an initial clinical trial in only 6 patients with brain tumor was indicated that 4DST PET was feasible for imaging brain tumors [9]. Toyota et al evaluated 4DST uptake and proliferative activity in 20 patients with gliomas, including 11 recurrent gliomas [10]. They showed a weak correlation between 4DST T/N ratio and Ki-67 index [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, imaging will only be used widely and routinely if it addresses an unmet clinical need that cannot be satisfied by competing technologies. In this respect, the capability of imaging is unique when used to guide surgery or 68 Mittra et al, 69 Bruehlmeier et al, 70 Kondo et al, 71 Yamamoto et al, 72 Toyota et al, 73…”
Section: Other Metabolic Tracersmentioning
confidence: 99%
“…Sustained retention of 18 F-FLT in tumors long after gadolinium-based contrast agents have washed out suggests an additional trapping process. Several papers (6,(9)(10)(11)(12) report a correlation between 18 F-FLT uptake in brain tumors, measured using SUV, and the histopathologic proliferation marker Ki-67. The correlation is usually quite weak, consistent with the thought that 18 F-FLT uptake is driven not just by proliferation but by additional mechanisms, such as BBB permeability and tumor blood flow.…”
mentioning
confidence: 99%